Perlindungan Hukum Terhadap Klien Akibat Tidak Diketahuinya Keberadaan Protokol Notaris dan Pejabat Pembuat Akta Tanah (PPAT) yang Meninggal Dunia - Yuniawaty Lunandi, Yenny; Tjoneng, Arman (UNES Law Review, 2024)
Notary and PPAT Protocols whose whereabouts are unknown and whose whereabouts are not known so that the protocol is not handed over will result in losses for clients using Notary and PPAT services because various data and files belonging to clients are stored by the Notary/PPAT so this becomes a legal issue related to protection legal clients who experience events like this. The type of research or approach method used is the normative legal research method and the approach used is the statutory approach. Based on research, when something like this happens, clients who experience the incident can contact the relevant agencies such as the Police, BPN and follow all established procedures.